Exploring the association between patient satisfaction and hospital quality in the United States - Sora Kang; Huazhi Liu; Charles Ledonio; Darwin Ang (PLoS ONE, 2026)
Background Patient experience is increasingly used as a public quality metric, but its relationship to hospital safety grades remains incompletely characterized because patient reported experience and technical safety measures capture different dimensions of care. Methods We performed a retrospective cross-sectional analysis of publicly available hospital level data from 2023. Leapfrog Hospital Safety Grades were linked with Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) patient experience scores. The linked dataset included 1,442 U.S. hospitals; 1,390 hospitals with letter grades A through F were included in grade stratified and regression analyses. HCAHPS domains were analyzed on a 1–5 scale, with higher scores indicating more favorable patient reported experience. One way ANOVA compared mean HCAHPS scores across Leapfrog grades. Multivariable logistic regression with hospital size adjustment evaluated HCAHPS domains associated with Leapfrog Grade A versus grades B through F. Results Mean HCAHPS domain scores declined across most domains as Leapfrog grades worsened from A to F. In multivariable analysis, nurse communication was associated with higher odds of receiving a Grade A safety rating (odds ratio [OR] 1.54, 95% confidence interval [CI] 1.11 to 2.13; p = 0.01), as was the hospital recommendation score (OR 1.54, 95% CI 1.15 to 2.06; p = 0.004). Doctor communication showed an inverse conditional association (OR 0.75, 95% CI 0.59 to 0.97; p = 0.03). Other HCAHPS domains were not independently associated with Grade A after adjustment. Conclusions Hospitals with higher Leapfrog safety grades generally had more favorable patient reported experience scores, and nurse communication and hospital recommendation were the most clinically interpretable independent predictors of Grade A status. The inverse association for doctor communication should be interpreted cautiously because HCAHPS domains are correlated and the analysis used hospital level cross-sectional data. These findings support the complementary role of patient experience in hospital quality assessment but do not establish causality.